From bodies as 'meat' to bodies as 'flesh': the expression of performance management as 'sacrificial acts' within professional rugby. Issue 4 (8th August 2019) - McConn-Palfreyman, Will; McInnes, Peter; Mangan, Anita
ABSTRACT: In this article, we argue that to extend the research on performance management we need to examine further how organisational members interweave the technology of such management into their work. Using Maurice Merleau-Ponty's philosophy, we question the notion that technology acts on bodies in a linear manner as 'meat' to be manipulated. His reversible ontology suggests that these materials can be woven into the flesh of organising in a multitude of ways. Specifically, we refer to professional rugby, and the manner in which its players utilise the technology of performance management, to forge a localised expression of sacrifice. We suggest that this expression provides a means for players to define and evaluate themselves against 'good rugby'. As forms of evaluation may vary in organisations, we recommend that researchers do not solely associate performance management with metrics but also look to other, more localised, expressions to inform their work.